Structural discrimination and social stigma among individuals incarcerated for sexual offenses: reentry across the rural–urban continuum - Huebner, Beth M. (Criminology, 2019)
The stigma associated with a felony conviction can impede the reentry process, and emerging research findings indicate that one's community can amplify or temper the mark of a criminal record. Researchers examining criminal stigma have focused on individuals living in urban areas, overlooking the experiences of persons outside these communities. Using qualitative data collected from a sample of men and women paroled for sexual offenses in Missouri, we contrast how social and structural stigma alter the reentry experiences for participants living in communities along the rural and urban continuum. The results show that the stigma of a sex offense conviction was a near‐universal experience and residence restrictions stymied efforts to find housing. Residents of urban areas and some large cities felt that the community offered relative anonymity from stigma but the stress of their status being discovered was omnipresent. Participants in rural areas and small cities had less social privacy and reported being shunned in the community, although strong social ties did mitigate some of the consequences of stigma. The results highlight the importance of considering place when studying reentry and have implications for designing correctional policies to address the needs of residents returning to non–metropolitan locations.